Interstitial lung disease in a female worker sensitized to epoxy resins: a case report submitted for discussion - Calisti, Roberto (La Medicina del Lavoro, 2016)
Epoxy resins are well known agents in respiratory medicine for their potential to induce bronchial asthma; the possibility of these agents causing respiratory diseases such as asthma, bronchitis, bronchiolitis obliterans with organizing pneumonia (BOOP) and similar lung diseases, has been poorly investigated. [...]